Strategi Kreativitas Guru dalam Menggunakan Gerak dan Lagu Sebagai Media Pembelajaran di TK Pertiwi Ngumbul 2 - Suprihatun Suprihatun; Latifatus Sa'adah; Helina Himmatul Ulya Lina (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to describe teachers’ creativity strategies in using songs and movement as learning media to enhance children’s engagement. The research employed a descriptive qualitative approach involving two Group B classroom teachers and 20 children aged 5–6 years. The findings indicate that teachers engaged in careful planning by selecting songs aligned with weekly themes, modifying lyrics to enrich vocabulary, and creating simple movements that were easy to follow. As a result, children’s engagement increased from 60% in the first session to 85% in the third session. The challenges encountered included limited song references, inadequate musical facilities, and differences in children’s motor abilities; these were addressed through tempo variation, repetition, and the use of body sounds. This study contributes to the enrichment of the literature on early childhood education teachers’ strategies in creating creative and varied learning experiences and may serve as a reference for developing music- and movement-based instructional methods.